SUKAWASTUDI KASUS PEMBACAAN AL-MA’TSURAT DI PONDOK PESANTREN MODERN DAAR EL-ISTIQOMAH NA KOTA SERANG SUKAWANA KOTA SERANG - nisa, Halyun; Nabila, Sofia Nurun; Rachmawati, Neti (Department of Ilmu al-Qur'an dan Tafsir, Faculty of Ushuluddin and Adab, State Islamic University of Sultan Maulana Hasanuddin Banten, Indonesia, 2023)
This article is a research report about the 'alive' Al-Qur'an at the Daar El-Istiqomah Modern Islamic Boarding School. Specifically, the Al-Qur'an verses contained in Al-Ma’tsurat which are read by male and female students are read regularly every morning and evening. This research does not examine the verses of the Qur'an as a text that must be understood with the meaning of several scientific disciplines, but using the Living Qur'an approach, this approach seeks to examine the form of interaction of Muslim groups towards the Qur'an in the aspect of applying the verses of the Qur'an. 'an to everyday life.